Pengaruh Price Discount, Bonus Pack, Dan Kualitas Pelayanan Terhadap Impulsif Buying ( Survei Pada Mahasiswa Dan Warga Umum Minimarket Al Khaibar Unisma Malang ) - Yasifah, Siti Ana; Nurhidayah, Nurhidayah; Arsyianto, Muhammad Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract Finding the price discount on impulsive purchases at Al-Khaibar Minimarket in Malang is The primary objective of this research. to ascertain the Al-Khaibar Minimarket Malang Bonus Pack on Impulsive Buying. At Al-Khaibar Minimarket in Malang, impulsive buying is used to assess quality service. Students at the Islamic University of Malang and members of the general public who shop at the Al Khaibar Unisma Malang minimarket make up the study's demographic. It's unclear how many people responded. The nonprobability sampling methodology combined with the purposive sampling technique a method for selecting samples based on specific considerations is the selection strategy employed in this investigation, resulting in 97 samples. A questionnaire is the method of data collecting, and SPSS is utilized for processing. The process of examining, classifying, organizing, analyzing, and confirming data in order to provide a phenomena social, scholarly, and scientific significance is known as data analysis. The study's findings demonstrated that impulsive purchasing is significantly impacted by price reductions and service quality. However, impulsive purchases in Malang City's Al-Khaibar Unisma Minimarket are not significantly impacted by the bonus bundle. Keywords : Impulsif Buying, Price Discount, Bonus Pack, Quality Service